Isolation and characterization of histones from healthy and cadang-cadang viroid infected cocos nucifera L. (coconut) - Estioko, Lucy P.
Initial attempts were made to isolate and partially characterize the histones from the coconut palm. The coconut chromatin where the histones were isolated from, was prepared from the coconut leaves using an extraction procedure standardized in this study. The histones isolated from the coconut chromatin consisted of an H2A-H2B fraction, H3 and H4. Characterization of these coconut histones included protein quantitation, molecular weight estimation, electrophoresis on 15% SDS-polyacrylamide and transverse 0-9 M urea gradient gels, and cunleosome reconstitution in linearized pCH 110 plasmid. The electrophoretic profile shown by SDS-polyacrylamide gel electrophoresis of the histones isolated from coconut was found to be similar with those from the various plant especies earlier studies which included wheat, barley, rye and pea. Also, the molecular weights obtained for eah of the coconut-derived histones were either exactly the same or within the range of values reported for most plant histones. These initial findings would seem to indicate that histone structure and function in plants are independent of the physiological complexity of the plant species. Observations made between the histones isolated from the healthy and the coconut cadang-cadang viroid-infected palms revealed an apparent increase in the histone content of chromatin, a higher affinity to the Coomassie Blue stain of some histone components, and a characterization electrophoretic pattern in the transverse gradient gel of those from the viroid-infected palms. These may suggect that histones play an important role in the pathogenesis of CCCVd in the coconut palm.